Sámi Nature-Centered Christianity in the European Arctic – Indigenous Theology Beyond Hierarchical Worldmaking (Nordic Journal of Practical Theology, 2023)
Bokanmeldelse av Tore Johnsens "Sami Nature-Centered Christianity in the European Arctic: Indigenous Theology Beyond Hierarchical Worldmaking". Anmeldelsen er skrevet av Tor Berger Jørgensen.